Cutting testing costs by the pooling design - Čvokić, Dimitrije D. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The purpose of group testing algorithms is to provide a more rational resource usage. Therefore, it is expected to improve the efficiency of large–scale COVID-19 screening as well.Methods: Two variants of non–adaptive group testing approaches are presented: Hwang’s generalized binary–splitting algorithm and the matrix strategy.Results: The positive and negative sides of both approaches are discussed. Also, the estimations of the maximum number of tests are given. The matrix strategy is presented with a particular modification which reduces the corresponding estimation of the maximum number of tests and which does not affect the complexity of the procedure. This modification can be interesting from the applicability viewpoint.Conclusion: Taking into account the current situation, it makes sense to consider these methods in order to achieve some resource cuts in testing, thus making the epidemiological measures more efficient than they are now.
Keywords: pooling design; group testing; Hwang’s generalized binary-splitting algorithm; matrix strategy; COVID-19; SARS-CoV-2